2009
DOI: 10.1105/tpc.108.059329
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Repeats of a Promoter Segment Causes Transcription Factor Autoregulation in Red Apples

Abstract: Mutations in the genes encoding for either the biosynthetic or transcriptional regulation of the anthocyanin pathway have been linked to color phenotypes. Generally, this is a loss of function resulting in a reduction or a change in the distribution of anthocyanin. Here, we describe a rearrangement in the upstream regulatory region of the gene encoding an apple (Malus 3 domestica) anthocyanin-regulating transcription factor, MYB10. We show that this modification is responsible for increasing the level of antho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
423
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(456 citation statements)
references
References 59 publications
15
423
2
Order By: Relevance
“…The aberrant expression of MYB could be caused by promoter sequence variations, such as insertion of transposons (Kobayashi et al, 2004) and other sequences (Espley et al, 2009) into the promoter region, and additionally by promoter methylation (Cocciolone and Cone, 1993;Telias et al, 2011). In this study, the expression of PcMYB10 was much lower in MRB-G fruit than in MRB fruit (Fig.…”
Section: Methylation Of the Pcmyb10 Promotermentioning
confidence: 56%
See 2 more Smart Citations
“…The aberrant expression of MYB could be caused by promoter sequence variations, such as insertion of transposons (Kobayashi et al, 2004) and other sequences (Espley et al, 2009) into the promoter region, and additionally by promoter methylation (Cocciolone and Cone, 1993;Telias et al, 2011). In this study, the expression of PcMYB10 was much lower in MRB-G fruit than in MRB fruit (Fig.…”
Section: Methylation Of the Pcmyb10 Promotermentioning
confidence: 56%
“…Transcription factors such as MYB are important regulators in the biosynthesis of anthocyanin in plants Ban et al, 2007;Gonzalez et al, 2008;Espley et al, 2009). The promoter region and expression pattern of PcMYB10 were analyzed in developing fruit of MRB and MRB-G.…”
Section: Expression Of Key Genes Involved In the Biosynthesis Of Anthmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the constitutive up-regulation of PAP1, ANT1, and MdMYB10 causes anthocyanin accumulation throughout the plant in pap1-D Arabidopsis (Borevitz et al, 2000), antl tomato (Solanum lycopersicum; Mathews et al, 2003), and red-fleshed apple (Espley et al, 2007). While overexpression of PAP1 and ANT1 MYB transcription factors is due to activation-tagged insertions in their promoter sequences (Borevitz et al, 2000;Mathews et al, 2003), the high transcript level of MdMYB10 was recently found to be due to the formation of a minisatellite-like structure comprising multiple repeats of a promoter segment that generates a novel autoregulatory motif (Espley et al, 2009). Unlike these reported anthocyanin-accumulating mutants, the Pr-D mutant appears to display a different mechanism in activating Pr expression.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge on the chemical variability among different apple cultivars will be useful to improve nutritional quality and promote future breeding with an alternative approach than genetic modification (Espley et al 2009). …”
mentioning
confidence: 99%